County Property Values and Tax Impacts of Florida's Citrus Industry - Alan W. Hodges; W. David Mulkey; Ronald P. Muraro; Thomas H. Spreen (EDIS)
Events impacting the citrus industry, such as citrus canker or increased foreign competition due to liberalization of trade barriers, may have a dramatic impact on the welfare of local communities. This paper provides estimates of the local fiscal impacts of ad valorem property taxes paid by citrus grove owners, and taxes generated by citrus processing operations. This is EDIS document FE437, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published November 2003.